(untitled) (Research, Society and Development, 2021)
Objective: to identify scientific evidence on strategies developed by nurses to promote good practices in the preparation and administration of medications aimed at patient medication safety. Method: This is an integrative review study, which sought to answer the following guiding question: What evidence is available in the literature about nurses’ strategies to promote good practices in the preparation and administration of medications? Results: among the nine selected articles, most were published in Portuguese and originated in Brazil, which may be a consequence of public health policies included in the Unified Health System (SUS), among them the National Patient Safety Program , which has been intensively institutionalized as a quality management tool in health services through patient safety goals . As for the levels of evidence, there was a predominance of level VI studies focusing on non-experimental descriptive studies on the subject. Conclusion: we show that despite the few identified productions, educational strategies and health technologies are being used and having significance for the promotion of the patient safety goal. It is hoped that this review will contribute to the clinical practice of nurses and may encourage the development of new studies on the subject.